Effect of antifibrotics on short-term outcome after bilateral lung transplantation: a multicentre analysis. Issue 6 (21st June 2018) - Lambers, Christopher; Boehm, Panja M.; Lee, Silvia; Ius, Fabio; Jaksch, Peter; Klepetko, Walter; Tudorache, Igor; Ristl, Robin; Welte, Tobias; Gottlieb, Jens
Interstitial lung diseases (ILDs) are a heterogeneous entity of diffuse parenchymal lung diseases characterised by damage of the parenchyma as a result of varying patterns of inflammation and fibrosis [1]. Idiopathic pulmonary fibrosis (IPF) is a specific subgroup of ILDs and has a devastating prognosis [2] with a median survival time of 2–3 years [2–4]. Pirfenidone (Esbriet) and nintedanib (Ofev) were approved for IPF treatment, showing a stabilisation of the disease [5, 6], and are the treatments recommended by international guidelines [1]. Nintedanib was shown to increase the risk of bleeding events in IPF patients during therapy [7] and the European Medicines Agency recommended discontinuation of nintedanib before major surgery but without a definite time frame for discontinuation [8]. Corticosteroids have been the conventional strategy used as treatment in different ILD subtypes despite limited evidence regarding their efficacy [9, 10]. After failure of medical therapy in severe ILD, lung transplantation (LuTx) represents an established therapeutic option in order to improve quality of life and survival [11]. New antifibrotic therapies do not impair the clinical course or survival of patients with interstitial lung disease who underwent bilateral lung transplantation http://ow.ly/7KoG30jyJmQ